Räumliche Aspekte des föderativen Systems — Eine Einführung - Fürst, Dietrich; Kilper, Heiderose (Raumforschung und Raumordnung | Spatial Research and Planning, 2005)
The discussion about the modernisation of German federalism is put in an international comparative context. The criticism of the traditional federalism of the Federal Republic of Germany is outlined and the pressure for adaptation that arises from the changed context conditions is sketched out. Different directions of development for changes and important points of departure for reform efforts in regional and institutional learning processes are found here.The process of “re-inventing the state” against the background of a changing conception of the state aims at a new division of labour between the federation, the federal states and the municipalities. In network-like forms of governance the federal states turn into “strategic general entrepreneurs”, while executive functions are transferred to the regions and municipalities. Regional planning would be the suitable co-ordinator for the growing need for co-ordination that accompanies this, under inclusion of the bodies that are addressed by the execution.